Time spent watching television impacts on body mass index in youth with obesity, but only in those with shortest sleep duration - Daniel M Golshevsky; Costan Magnussen; Markus Juonala; Kung‐Ting Kao; Brooke E Harcourt; Matthew A Sabin (WILEY, 2022)
Aim To determine the interplay between sleep and sedentary behaviours on body mass index (BMI) in children with obesity. Methods Cross-sectional study of 343 children with obesity aged 4-17 years, from a tertiary care weight management clinic in Melbourne, Victoria, Australia. Multifaceted data relating to activity and sleep from child and parent questionnaires analysed with anthropometric data collected during routine clinical care. Associations between sleep duration and activity measures were examined via regression models with adjustment for potential confounders. Results Higher BMI was associated with more hours spent watching television (P = 0.04), as well as less reported enjoyment of physical activity (P = 0.005) and less time spent in organised sport activity (P = 0.005). Higher BMI was also associated with higher levels of obstructive sleep apnoea (P = 0.002). Less time in bed was associated with higher levels of BMI (P = 0.03) but analysis by sex revealed this association to only hold for males. In the whole group, a significant television and sleep interaction was seen, such that increasing television watching was associated with higher BMI, but only in those with shortest sleep duration. Conclusions Both poor sleep and increasing screen time (including television viewing, smart-phone use, internet use or video-gaming) appear to impact BMI in children with obesity, with a particular detrimental effect of television viewing in those who sleep less. Efforts to improve sleep time and quality in children may minimise negative effects of screen time on increasing BMI and should be included in public health strategies to combat obesity in childhood.